Acute Keratoconus-Like Hydrops after Laser In Situ Keratomileusis - Carsten H. Meyer; Stefan Mennel; Jörg C. Schmidt (Journal of Ophthalmology)
Purpose. To demonstrate keratoconus-like hydrops after laser in situ keratomileusis (LASIK) by optical coherence tomography (OCT). Patient and Methods. A 21-year-old man received uneventful bilateral LASIK. On slit lamp examination or corneal topography there were no signs of fruste keratoconus. The preoperative corneal thickness was 587-𝜇m OD and the calculated ablation for two treatments was 114-𝜇m. Uneventful LASIK with an optical zone of 7 mm and an ablation of 89-𝜇m OD, and an ablation of 73-𝜇m OS was performed. Three years postoperatively, he complained about progressive myopia and impaired vision OD. His VA was hand motion OD and 20/20 OS. Results. OCT and light microscopy revealed an anterior corneal steepening and acute keratoconus-like excessive edematous swelling. Conclusion. The cornea is mechanically weakened after LASIK by the lamellar cut and tissue subtraction. Although the advocated minimal residual stromal bed thickness is 250-𝜇m, it may not be adequate to prevent progressive keratoconus-like hydrops in the selected cases.